Effectiveness of COVID-19 Antivirus Therapy and Its Relationship with Vaccination: A Retrospective Analysis - Andi Utari Prasetya Ningrum; Retnosari Andrajati; Nadia Farhanah Syafhan; Aditya Wirawan (Jurnal Respirologi Indonesia, 2023)
Background: COVID-19 is known to have infected more than a million people. COVID-19 can be treated with antivirals. Besides antiviral drugs, vaccination becomes one of the strategies to suppress the spread of COVID-19. This study aimed to analyze the effectiveness of antivirus and the relationship between vaccination and the effectiveness of the two antiviral therapies in COVID-19 patients based on improvements in the patient's clinical condition, length of stay, and mortality.Methods: This study used a retrospective cohort design conducted at the Universitas Indonesia Hospital, Depok, Indonesia. Data were taken from medical records and hospital databases from January 2021 to August 2022. The antivirals in this study were remdesivir and favipiravir. The samples were divided into two groups, namely the vaccinated and unvaccinated groups.Results: The factor affecting the effectiveness of remdesivir and favipiravir therapy was the severity of COVID-19. It was shown that vaccination had a significant effect on improving clinical conditions, reducing length of stay, and reducing mortality in patients treated with remdesivir who had been vaccinated compared to those who had not been vaccinated. In patients who received favipiravir therapy and were vaccinated, it also showed an effect on improving clinical conditions, length of stay, and mortality compared to patients who were not vaccinated, although the results were not statistically significant.Conclusion: Vaccination had a positive effect on the effectiveness of remdesivir and favipiravir in COVID-19 patients, which could improve the patient's clinical condition in a better direction, as well as reduce length of hospitalization and mortality.